Facilitation qualities of the future teacher - Prokopenko, Iryna (Journal of Education, Health and Sport, 2020)
The realities of today require active, creative future professionals who are trained in pedagogical universities. Therefore, in order to intensify the educational activities of students, special attention should be paid to the organization of facilitation interaction in the following dyads: "teacher-group", "teacher-student", "student-group", "student-student". Currently, insufficient attention is paid to the problem of facilitation interaction between teachers and students. If in the traditional conditions the organization of the educational process is possible on the basis of facilitation interaction, then in the conditions of the pandemic (COVID-19) teachers and students had to face unexpected difficulties due to the introduction of self-isolation. The author proved that if the system of higher education still functioned quite effectively online, the school education system was not ready for self-isolation. In Ukraine, by March 2020, less than 1% of students studied remotely. It should be noted that the closure of general secondary education and the emergency transition to distance learning are associated with obvious problems, mainly due to insufficient technical equipment, lack or insufficient training of both teachers and students to work in a pandemic. The author raises the problem that the organization of facilitation interaction of teachers with students requires the formation of the teacher’s facilitation qualities.